PENGARUH BUDAYA ORGANISASI TERHADAP INOVASI PRODUK PADA TV BERITA MILIK PEMERINTAH INDONESIA (STUDI KASUS PADA LPP TELEVISI REPUBLIK INDONESIA) - Ardino Yosland Putranto; Wahyuningsih , (Media Riset Akuntansi, Auditing & Informasi, 2012)
In the era of open competition and is very tight at this time, product innovation is not an option but a necessity. The changes and dynamics in market and also the environment in general, can not be ignored if you want to continue to survive in the business. Accordingly, this case study attempted to analyze on product innovation, particularly in relation to organizational culture. Case studies conducted at the Institute for Public Broadcasting (LPP) Televisi Republik Indonesia (TVRI) as a government-owned TV station news which is also the oldest TV station in Indonesia. The analysis focused on the influence of organizational culture - which includes the type of adhocracy and hierarchy culture - to product innovation in TVRI. Data were obtained through questionnaires to managers and staff of the news division field. With the method of multiple regression analysis, the results suggest that there are cultural influences of organizational culture that include adhocracy and hierarchyculture to product innovation either jointly or individually. The type of culture that encourages more product innovation happening in the LPP TVRI is adhocracy culture. This indicates that TVRI should immediately make the transition a culture that has been more dominant, the hierarchy culture, toward a more flexible and responsive to environmental changes, which is adhocracy culture. Thus expected to be able to support its role in maximazing the function of public institutions to provide more balanced information on the people of Indonesia.